Design, Synthesis, and Pharmacological Evaluation of Novel Hybrid Compounds to Treat Sickle Cell Disease Symptoms. Part II: Furoxan Derivatives - Dos Santos, Jean Leandro [UNESP]; Lanaro, Carolina; Chelucci, Rafael Consolin [UNESP]; Gambero, Sheley [UNESP]; Bosquesi, Priscila Longhin [UNESP]; Reis, Juliana Santana [UNESP]; Lima, Lidia Moreira; Cerecetto, Hugo; Gonzalez, Mercedes; Costa, Fernando Ferreira; Chin, Chung Man [UNESP] (Amer Chemical Soc, 2012)
Phthalimide derivatives containing furoxanyl subunits as nitric oxide (NO)-donors (3a-g) were designed, synthesized, and evaluated in vitro and in vivo for their potential uses in the oral treatment of sickle cell disease symptoms. All compounds (3a-g) demonstrated NO-donor properties at different levels. Moreover, compounds 3b and 3c demonstrated analgesic activity. Compound 3b was determined to be a promising drug candidate for the aforementioned uses, and it was further evaluated in K562 culture cells to determine its ability to increase levels of gamma-globin expression. After 96 h at 5 mu M, compound 3b was able to induce gamma-globin expression by nearly three times. Mutagenic studies using micronucleus tests in peripheral blood cells of mice demonstrated that compound 3b reduces the mutagenic profile as compared with hydroxyurea. Compound 3b has emerged as a new leading drug candidate with multiple beneficial effects for the treatment of sickle cell disease symptoms and provides an alternative to hydroxyurea treatment.